Why so Silent on the Right to Silence? Missing Matters in the Review of the Evidence Act 2006 - McDonald, Elisabeth (Victoria University of Wellington Law Review, 2013)
In this article I examine the scope and application of ss 32 and 33 of the Evidence Act 2006 (NZ) with reference to both the historical justification for the right to silence and the legislative history of these provisions. In considering the extent to which the sections do not reflect either the recommendations of the Law Commission in 1999, nor Parliamentary intent, I question why the sections were left out of the Commission's first statutory review of the Act in 2013. I conclude by suggesting that the right to silence should be the subject of informed public debate and raise some possible options for reform.